The Effect Of Self Efficacy, Work Discipline And Perceived Organizational Support (Pos) On Affective Commitment - Septiana Dwi Rahayu (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study examines the influence of self-efficacy, work discipline, and perceived organizational support (POS) on affective commitment among employees of PDAM Tirta Handayani, Gunungkidul Regency. As a public water utility, the organization faces complex operational challenges, including sustainable drinking water management, service reliability, and serving a large, diverse customer base. Understanding determinants of affective commitment is crucial, as employees' emotional attachment drives service quality, organizational stability, and long-term performance.The research investigates how self-efficacy, work discipline, and POS individually and collectively shape employees' emotional bonds with the organization. A quantitative approach was employed, collecting primary data from PDAM employees via a Likert-scale questionnaire. Data analysis used SPSS version 26, including validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression. Hypothesis testing involved t-tests and F-tests to ensure result robustness.Findings reveal that self-efficacy has no significant effect on affective commitment, indicating personal confidence alone is insufficient in this context. Conversely, work discipline and POS exert strong positive influences. Overall, these variables collectively enhance affective commitment, underscoring the vital role of organizational practices and support systems in public service entities.